ANALISIS KINERJA SOSIAL DAN KINERJA KEUANGAN LEMBAGA KEUANGAN MIKRO (LKM) USAHA EKONOMI KELURAHAN-SIMPAN PINJAM (UEK-SP) MAHARATU JAYA KELURAHAN MAHARATU KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Sandi Setiawan; Ahmad Rifai; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research was conducted in Microfinance institutions (MFI) UEK-SP Maharatu Jaya, Pekanbaru. The purpose of this study to analyze the social performance and financial performance of MFI UEK-SP during 2009-2013. Social performance was analyzed using mixed market performance indicators and financial performance was analyzed by using the 17 indicators of PEARLS. Social performance analysis show that MFI UEK-SP has achieved its mission and social objectives, was indicated the indicator of increasing of total loan volume revolving at 25.58 percent. Result also show that the highest increasing of lending revolving  is trading sector (31.00 pecent), and the increasing of poor lending volume as much as 18.13 percent. Financial performance analysis shows that the 8 ratio of PEARLS is ideal goals, that are  the ratio of current assets, loans from the outside, the capital of institutions, non-productive assets, income from loans, asset growth, net income and capital growth. While the 9 ratio of PEARLS less than ideal goals, that are the ratio of the risk reserve fund for loans negligence 1-12 months and over 12 months, outstanding loans, operating costs, non perfoaming loan, loan growth, liquidity and deposit growth stocks. Keywords: Financial Performance, Microfinance Institution, Social Performance, BEV-SL